Isolation and characterisation of bovine ultralong antibodies to SARS-CoV-2 using phage display - Park, Emily (2024)
The urgency for therapeutics in the arms race against SARS-CoV-2 increases with the emergence of each novel variant. Although current vaccines provide protection against severe disease in the majority of the population, there is still a great need for therapeutics for immunocompromised and severely ill patients. Broadly neutralising antibodies are highly adept at binding conserved epitopes, and, with a short developmental timescale, they are ideal candidates for antibody therapies.